Dynamiques stratégiques autour de la forêt classée de l’Alibori Supérieur au Bénin - Yarou Guera Chabi Yoro; Rose Kikpa Bio (VertigO, 2025)
Forest ecosystems, which provide multiple goods and services to humans, face various anthropogenic and climatic pressures. However, the establishment of certain protected areas by authorities alters the lifestyle and organization of local populations, particularly in Africa. This research analyzes the factors contributing to the degradation of the Alibori Superieur Classified Forest in Benin. The primary data collection methods used were semi-structured interviews and cartographic data analysis. Sampling was based on purposive selection targeting a diverse profile, followed by the snowball technique, which enabled interviews with fifty participants, including forest rangers, local elected officials, and neighboring populations. This research draws on the strategic perspective of Crozier and Friedberg (2014). Geospatial results show a significant reduction in the forested area, with open forest and wooded savannah decreasing from 57,911 ha in 2000 to 4,740 ha in 2022. Furthermore, the data reveal that the clandestine expansion of agricultural lands and agropastoral activities within the forest by neighboring populations are the primary causes of this degradation. Additionally, the management and conservation regulations implemented have led to circumvention strategies, thereby accelerating the degradation and overexploitation of natural resources. Local populations, who have inhabited the area for several generations long before the forest was classified in 1955, maintain a deep-rooted sense of belonging and legitimate rights to these lands, which they perceive as their ancestral heritage. This connection, combined with their livelihood activities centered on agriculture and livestock farming, poses a persistent threat to the ecosystem's balance while exacerbating tensions among the forest's various users.